Some triple block intersection numbers of Paley 2-designs of QN-type - Raposa, Blessilda P. (Animo Repository, 2001)
We determine some possible values for the cardinality of the intersection of three blocks from Paley 2-(2q + 1, q, (q - 1)/2) designs where q is a prime power such that q ≡ 1 (mod 4).